PECULIARITIES OF THE MATURE PINE STANDS FORMATION AFTER SURFACE FIRES - Sydorenko, S. G.; Voron, V. P.; Melnik, E. E.; Sydorenko, A. G. (Forestry and Forest Melioration, 2018)
Introduction Fires are considered to be one of the most dangerous phenomena for forests resulting in catastrophic economic, environmental and social losses. Accurate prediction of mortality extent and probability of occurrence is possible on the ground of regional studies after consideration of specific features of the species, the most important morphological and inventory indices of trees, the types and degree of damage. Therefore, the development of methods for post-fire mortality prediction is extremely important for Ukrainian forests. The aim of the study was to reveal peculiarities of stands formation during first years after surface fires. Methods and Objects Permanent sample plots (PSP) were established by conventional methods in forestry in mature and overmature pure pine stands damaged by surface fire in the Left-bank Forest Steppe of Ukraine. During the processing of the material correlation and regression analyses were used. Differences in the post-fire growth after summer and spring surface fires were analyzed by F-test (comparison of sample particles). To establish mortality factors for old pine trees the litter thickness was measured at various distances from the trunk, every 30 cm from the base of the trunk up to 90 cm. The measurements of bark thickness at the bottom of the trunk (5 cm above the level of the litter) and below the litter with accurance of 0.1 mm was conducted for the sample trees. Results and Conclusion It has been established that spring and summer fires have different effects on mature pine forest stands. Greater mortality exactly after summer fires as compared to that after spring is statistically significant (Ff = 154,6; F0.001 = 11; р < 0.001 ). In fact, the share of the tree mortality after summer fires was 10 times higher than after spring ones (53.1 % vs. 5.3 %). A high reliable relationship was determined between mortality rate and height of bark scorch (r = 0.93, tf = 6.4, t0.01 = 2.45, R? = 0.87. To determine the reaction of trees of various maturities on the fire damage, the tables of tree mortality including natural degree of thickness and average height of bark scorch were constructed. It has been found that the most depressed trees die after any damage; the most developed trees with highest degree of thickness also react extremely badly after damaging (their tree mortality is 48–55 % at minimal damage and 100 % for bark scorch height greater than 1 m). So, thicker trees were less resistant to fire damage. A notable trend is that proportion of dead trees increased with the increasing trees diameter. There is a very strong direct correlation (tf =5.84, t0.01 = 3.71, р = 0.01) between the study variables. Summer fires were catastrophic for mature pine trees, especially for the most thick of them. One of the primary reason of the most developed trees’ mortality is accumulation of more thick forest litter under the base of the tree trunk and, as a consequence, the maximum damage of this particular part of the tree. The forest litter thickness ranges from 7 to 15 cm at the base of the trunk (11.000 ± 0.518 cm an average) and decreases with increasing distance from the trunk to 2.6 ± 0,30 cm (Ff = 56.8; Ft = 2.7; p<0.001). It has been found that the bark thickness at the litter level is 2.5 times thinner than one above the litter level – 8.8 ± 0.99 mm and 22.2 ± 2.29 mm, respectively. Differences in the sample trees bark thickness have been confirmed statistically (tf = 5.54; t0.05 = 2.26). Therefore, at the surface fire, when complete combustion of the litter stratum occures, root systems and the lowest part of the trunk have sustained extensive damage, which lead to intensive mortality. Unlike the young and middle-aged trees for which resistance to fire damage typically increases with increasing of diameter, the mature pine forests after summer fires have the opposite effect.